1996
DOI: 10.1002/(sici)1096-9071(199604)48:4<339::aid-jmv7>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C plasma viral load is associated with HCV genotype but not with HIV coinfection

Abstract: The influence of human immunodeficiency virus (HIV) coinfection and hepatitis C virus (HCV) genotype distribution on HCV viral load and alanine amino transferase (ALT) levels in chronically infected patients remains unclear. In the present study, serum samples from a group of haemophiliac patients were investigated retrospectively. HCV geno- and subtyping was carried out using the Inno line probe assay (Inno LIPA, Innogenetics, Zwijnaarde, Belgium) in 87 patients positive by HCV RT PCR. Of these patients, 31 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
3
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 22 publications
2
12
3
2
Order By: Relevance
“…This study contradicts with Berger et al study [26] in which no correlation was seen between HIV infection and HCV viral load. The results of the current study revealed a strong correlation between HCV viral load and HIV co-infection as well as GT1 HCV genotype.…”
Section: Discussioncontrasting
confidence: 89%
“…This study contradicts with Berger et al study [26] in which no correlation was seen between HIV infection and HCV viral load. The results of the current study revealed a strong correlation between HCV viral load and HIV co-infection as well as GT1 HCV genotype.…”
Section: Discussioncontrasting
confidence: 89%
“…First, the risk of hepatotoxicity following initiation of antiretroviral drugs is greater in patients infected with HCV genotype 3 than in those infected with other genotypes [34][35][36][37]. Second, the use of some antiretrovirals could favor steatosis of the liver [27,[38][39][40][41]. In summary, HCV genotype 3 and antiretroviral therapy might be synergistic, together causing liver steatosis and indirectly accelerating the progression of liver fibrosis in HCV-HIV-coinfected patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, one report suggests that this may be the case only in patients infected with HCV genotype 1. 54 An association between serum HCV viral load and saliva HCV viral load has also been recently demonstrated, which may have major implications for HCV transmission in coinfected patients. 55 Together, these data demonstrate a higher rate of vertical and sexual transmission of HCV in coinfected patients, and that HIV is a cofactor for HCV transmission.…”
Section: Transmissionmentioning
confidence: 95%